Towards an integrated cereal crop-forage production for improved cattle productivity: The Malawi experience - Munthali, J.T.K.; Msiska, H.D.C.; Zimba, A.W.C.; Dzowela, B.H. (International Livestock Centre for Africa, 1990)
Reviews available information in the field of integrating cereal-crop-forage production, the degree of acceptance of success or failure and suggestions for improving the system in Malawi. Examines grain, maize stover and legume forage dry matter yields in maize-forage legume mixed cropping, grain yield of maize grown as an intercrop with selected food legumes, total dry matter yield and crude protein yield in maize-forage legume-mixed cropping and liveweight changes and daily intake of roughage dry matter of steers fed maize forage legume combinations. Presents soil analysis results and proportion of legume dry matter in total dry matter. Discusses available technology, lessons learnt and utilization of research results. Ends with suggestions to improve the utilization of forage research results.